First report of decompression sickness (DCS) in a sei whale (Balaenoptera borealis) stranded in southern Peninsular Malaysia - Lokman, Norina; Arshat, Norsharina; A. H., Nurnadiah; Kalam, Sarol; M. T., Nurliyana; Fahmi,; M., Aida; Mohamed Mustapha, Noordin; Abd Rahman, Nor Yasmin; M. D., Hassan; I., Kamaruddin; M. N., Munir; et al. (Department of Veterinary Services Malaysia, 2017)
Decompression sickness, a condition in whales caused by bubble formation in certain body tissues from dissolved inert gases. It occurs during transition from a high pressure environment to one of lower pressure, resulting in a range of conditions from itching to joint pain, convulsions, and death. A carcass of a stranded Sei Whale, Balaenoptera borealis, found on the shores of southern coast of Peninsular Malaysia was presented for postmortem. Investigation results showed that the male Sei Whale, named Si Corner showed pathologic lesions as seen from histology with the formation of fibrosis, emphysema and edema in the lungs and hepatic atrophy which indicated chronic starvation. It believed that he also suffering from “Barotrauma or decompression sickness” which affected the ear or lungs which lead to unbalanced movement due to changes in air pressure. This may have caused the whale to beach and consequent mortality. The pathologic lesions found give an insight into possible causes of death of beached whales in Malaysia.